The Chemistry of Food Additives and Preservatives. - Msagati, Titus A. M. (Wiley, 2012)
The Chemistry of Food Additives and Preservatives is an up-to-date reference guide on the range of different types of additives (both natural and synthetic) used in the food industry today. It looks at the processes involved in inputting additives and preservatives to foods, and the mechanisms and methods used. The book contains full details about the chemistry of each major class of food additive, showing the reader not just what kind of additives are used and what their functions are, but also how they work and how they can have multiple functionalities. In addition, this book covers & n.